Shallow-water brittle stars (Echinodermata: Ophiuroidea) from Araçá Bay (Southeastern Brazil), with spatial distribution considerations - Alitto, Renata A. S.; Bueno, Maristela L.; Guilherme, Pablo D. B.; Di Domenico, Maikon; Christensen, Ana Beardsley; Borges, Michela (Zootaxa, 2018)
The detailed study of arm ossicles, particularly the lateral arm plates, is providing valuable information in the elucidation of ophiuroid taxonomy. The present study describes in detail 16 species of brittle stars from Araçá Bay, Brazil. This information is used to construct the first interactive electronic key, providing a valuable resource for a broad range of researchers. Brittle stars families were divided into three groups based on their spatial distribution: i) infaunal species of intertidal and shallow subtidal belonging to Amphiuridae and Ophiactidae, ii) epizoic species belonging to Amphiuridae, Ophiactidae, and Ophiotrichidae and, iii) epifaunal species of the subtidal belonging to Ophiodermatidae and Hemieuryalidae. In the global context of recent revisions of ophiuroid taxonomy, the present work provides additional characters for use in future phylogenetic studies.